Implicaciones económicas de la masa monetaria en la inflación de Ecuador: un análisis de ventajas y desventajas, periodo 1990-2022 - Cajamarca Zapata, Leydi Gabriela (2024)
In Ecuador, the inflation rate has shown significant fluctuations during the post-pandemic period, reaching an index of 3.74% and achieving its highest level in December 2022. In this context, the objective of this study is to evaluate the incidence of the monetary mass on inflation in Ecuador, during the period 1990-2022, through statistical techniques and econometric models, to propose policy strategies that contribute to mitigate the impact of high inflation rates in the country. For this analysis, the World Bank and World Development Indicator [WDI] databases have been used to compile statistical data on the study variables, such as inflation, money supply, unemployment, gross national expenditure and foreign direct investment, which were used in econometric time series models. The main results show a negative relationship between the monetary mass and inflation; furthermore, they do not indicate an equilibrium relationship in the short or long term. An economic policy orientation is to implement a "Savings Incentives and Liquidity Control Program" with attractive interest rates for fixed-term deposits, financial education campaigns and temporary consumer credit regulations, seeking to reduce liquidity in the market, reduce pressure on prices and strengthen the country's financial stability.